Energy storage and transmission expansion planning: substitutes or complements?. Issue 8 (6th March 2018) - Bustos, Carlos; Sauma, Enzo; de la Torre, Sebastián; Aguado, José A.; Contreras, Javier; Pozo, David
Abstract : The massive development of energy storage systems (ESSs) may significantly help in the supply–demand balance task, especially under the existence of uncertain and intermittent sources of energy, such as solar and wind power. Using ESSs as complements of renewable generation has technical and economic consequences in both the short‐term operation and the long‐term expansion planning of the grid. The authors propose a transmission expansion planning model that incorporates decisions about the expansion of generic ESS units in order to study the interaction between the penetration and location of ESSs and the transmission investment decisions. The problem is formulated as a mixed‐integer linear programming model and considers different demand blocks and their correlation with renewable generation, to account for the distinct features of the system over time. The authors' results show that ESSs are not only substitutes of transmission assets, but they may also be complemented with transmission assets depending on the power system characteristics. They use a 27‐bus representation of the main Chilean network to illustrate the model proposed and to highlight some interesting results about the potential complementarity of ESSs and transmission expansion.